Changing the Unions' Agenda: Women's Activism in Australian Trade Unions in the 1970s and 1980s. (November 2019) - Strachan, Glenda
Abstract : This paper takes a preliminary look at women's activities in trade unions in the 1970s and 1980s and the ways in which women's activism changed unions through the instigation of the Working Women's Charter, women's committees and training for women. Women's activism in trade unions created distinct spaces for women to support each other, to develop policies and to work together for their acceptance and adoption within unions. This resulted in major changes to policies that addressed women's specific needs within trade unions and in the wider society. The activism of the 1970s and 1980s formed the foundation for ongoing changes in policies and representation in trade unions. This article focuses on the experiences of women as they worked within unions to make changes and charts some of the major changes at the national level of the Australian Council of Trade Unions. It draws on a limited range of sources and the author's own experiences of the time.